Methane emission from forage-fed sheep, a study of variation between animals : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Animal Science in the Institute of Veterinary, Animal and Biomedical Sciences, College of Sciences, Massey University, Palmerston North, New Zealand - Pinares-Patiño, C. S. (Massey University, 2000)
Rumen methanogenesis represents a loss of between 2 to 15% of the energy intake by the animal, and methane (CH4) has a role in the global warming phenomenon. Thus, any reduction of ruminant CH4 emission would have both environmental and nutritional benefits. The development of cost-effective strategies to mitigate ruminant CH4 without causing a negative impact on animal production, especially for systems based on forages, is a major challenge. Large between-sheep (within a breed) variations in CH4 emission, under controlled and grazing conditions, have been described in the literature (Chapter 1). This thesis studied the nature and causes of the between-sheep variation in CH4 emission, with the objective of using it as a tool to reduce CH4 emission. The sulphur hexafluoride (SF6) tracer technique was used to measure CH4 emission throughout this study, therefore three trials were conducted with penned sheep in order to evaluate this technique against the standard respiration chamber (Chapter 2). Poor ventilation in the building and prolonged in rumen deployment of the SF6 permeation tubes were identified as reasons for poor agreement between the techniques in the initial trials. However, when these problems had been overcome, good agreement (r=0.79, p=0.02) between the techniques was found, with the tracer CH4 values being 10% lower than the chamber values. The tracer technique was then used to screen grazing sheep for their rates of CH4 emission, and three groups of sheep (8, 10 and 8 animals), each comprising sheep with low or high CH4 emissions, were selected, and their CH4 emissions were monitored during 12, 12 and 5 months, respectively (Chapter 3). This study showed that sheep did not maintain their rankings with respect to CH4 emission when they were brought from pasture to restricted indoor feeding conditions. However, they did maintain their rankings under generous grazing conditions, although the persistence of rankings weakened with time. A detailed study of rumen digestion (Chapter 4) was carried out with sheep fed indoors on lucerne hay at a restricted level (1.2 maintenance). This study revealed that particulate fractional outflow rate from the rumen (particulate FOR, % h-1) explained a large proportion (R2=0.57) of the between-animal variation in CH4 emission (%GEI). In addition to the negative relationship to CH4 emission (%GEI), particulate FOR was negatively correlated with rumen fill (g) (r=-0.69, p=0.03) and with digestibility of cellulose (r=-0.65, p=0.04). Based on the latter results, a simple field index for screening grazing sheep for rumen particulate FOR or rumen volume, based on changes in liveweight, was tested (Experiment 1, Chapter 5). LW change during short-term grazing, following overnight fasting, was strongly correlated with maximum rumen fill (determined at the end of evening grazing). This index was used to screen sheep and to select 10 sheep with 'small' rumen volumes and 10 sheep with 'large' rumen volumes. However, this index was not repeatable in subsequent measurements (Experiment 2, Chapter 5). In a later study (Chapter 6), sheep (6 animals) and alpaca (6 animals), two animal species with known differences in forestomach particulate FOR (lower in alpaca), were successively fed ad libitum on three different forages: (1) indoors on chaffed lucerne hay, (2) grazed on ryegrass/white clover pasture (RG/WC), and (3) grazed on Lotus corniculatus pasture (Lotus). In general, the quality of diets selected by the sheep, their voluntary feed intakes (per kg metabolic liveweight) and their CH4 emissions (g d-1) were higher than those of alpaca, but their CH4 emissions per unit of intake (%GEI) were lower than those of alpaca. On lucerne hay, the digestibility of cell walls was higher and the urinary energy loss lower in alpaca than in sheep. The sheep produced much less CH4 (%GEI) while grazing on Lotus than on the other feeds, whereas alpaca grazing Lotus showed low values for apparent digestion of cell walls. In conclusion, this thesis showed that particulate FOR, an animal-related factor, was a major contributor to the between-sheep variation in CH4 emission (%GEI) and particulate FOR was also suggested to be the underlying mechanism by which alpaca and sheep differed in their rates of CH4 emission (%GEI). Sheep ranked initially low or high for CH4 emission rates (%GEI) persisted in their rankings only under generous grazing conditions and this persistence weakened with time. Changes in diet selection or particulate FOR in response to the seasonal changes in pasture quality and composition may have been the reasons for the weakened persistence in CH4 emission. Future developments in techniques which can measure between-sheep differences in particulate FOR or rumen volume with large numbers of animals under grazing will be useful in the assessment of the benefits of these animal factors for CH4 mitigation. The depressing effect of Lotus corniculatus on CH4 emissions by sheep shown in this study represents another benefit of condensed tannin-containing temperate legumes for sustainable pastoral production systems.
Keywords: Sheep; Feed utilisation efficiency; Feeding and feeds; Atmospheric methane; Methane metabolism; New Zealand